2013
DOI: 10.1155/2013/815840
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive Keratectomy with Adjunctive Mitomycin C for Residual Error after Laser-Assisted In Situ Keratomileusis Using the Pulzar 213 nm Solid-State Laser: Early Results

Abstract: Purpose. To evaluate the accuracy, efficacy, stability, and safety of photorefractive keratectomy (PRK) enhancement using the Pulzar 213 nm solid-state laser (SSL) with adjunctive Mitomycin C in eyes previously treated with laser assisted in situ keratomileusis (LASIK) with residual error of refraction. Methods. This is a prospective noncomparative case series of 16 eyes of 12 patients who underwent PRK for residual refractive error after primary LASIK. Mitomycin C 0.02% was used after the PRK to prevent haze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…It should be pointed out that the initially obtained good results described above could be achieved without a nomogram and match the previously reported good safety and efficacy profiles reached with solid-state lasers of other research groups [ 17 , 18 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It should be pointed out that the initially obtained good results described above could be achieved without a nomogram and match the previously reported good safety and efficacy profiles reached with solid-state lasers of other research groups [ 17 , 18 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, based on the work of Hale and Querry on extinction coefficients of radiation over a large area of the electromagnetic spectrum, Dair and co-workers found less absorption of up to two orders of magnitude for solid-state lasers in Balanced Salt Solution (BSS) and 0.9% Sodium Chloride solution compared to an excimer system [ 19 , 20 ]. While for excimer lasers emitting at 193 nm, tissue hydration control was found to be crucial to achieve target ablation [ 21 , 22 , 23 ], solid-state ablation lasers emitting at longer wavelengths would offer the benefits of being less dependent on the hydration state of the cornea and the humidity of the surgical environment, as well as not using toxic gas and operating silently [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beerthuizen and Siebelt [ 31 ] reported prolonged grade 1 corneal haze that persisted up to 6 months in 1 eye in their study that included 18 eyes treated with PRK for residual ametropia after LASIK. In another prospective study [ 37 ] on 16 eyes treated with PRK and mitomycin C (50 seconds) for residual error following LASIK, none of the eyes developed corneal haze of any degree during 6-month followup. A study reported that exposure to high ultraviolet radiation level may increase the risk of late-onset corneal haze in eyes with moderate to high myopia [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several publications using surface retreatment after LASIK after Carones, most of them including only a limited number of eyes. [9][10][11][12][13][14][15][16][17] Table 2 shows safety and accuracy data in these studies. Our study includes a large number of eyes with at least 24 months follow-up.…”
Section: Discussionmentioning
confidence: 99%